IMPLEMENTATION OF A SEPIC CONVERTER IN AN OFF-GRID SOLAR POWER PLANT (PLTS) USING FUZZY LOGIC METHOD WITH A HAIWELL SCADA-BASED MONITORING SYSTEM - Putra, Kurniawan Eka; Yunior, Yudhis Thiro Kabul; Sukma, Meita Maharani (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
Indonesia has great potential for solar energy. Solar energy has great potential to be utilized as an energy source. Solar cell devices (photovoltaic/PV) are needed to be used as power plants by connecting solar panels to solar charge controllers. This study aims to implement a SEPIC converter in an off-grid Solar Power Plant (PLTS) to stabilize the output voltage and monitor the system using SCADA HAIWELL. The SEPIC converter works by combining the working principles of buck and boost converters. The main components of the SEPIC converter are two inductors, two capacitors, and two switches. The switch used in this study is a MOSFET controlled by a NodeMCU microcontroller using the fuzzy logic method. The microcontroller also processes data from the INA219 sensor that measures voltage and current. The data is then sent to SCADA HAIWELL to be monitored in the form of HMI. The test results show that the system that has been built can work well. The SEPIC converter successfully stabilizes the output voltage of the solar panel at 14V and charges the battery efficiently. SCADA Haiwell can also monitor the system in real-time and provide accurate information about system conditions. Thus, this system can be used to optimize the performance of off-grid PV power plants.